THE EFFECT OF WORK ETHIC, POSITION MUTATION, AND JOB SATISFACTION ON LECTURER PERFORMANCE WITHIN THE FACULTY OF ECONOMICS AND ISLAMIC BUSINESS UIN ALAUDDIN MAKASSAR - Gani, Nuraeni; Suwandi, Memen (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This study aims to analyze the effect of work ethic, job transfer, and job satisfaction on lecturer performance at the Faculty of Economics and Islamic Business, State Islamic University of Alauddin Makassar. The background of this research is the importance of these factors in improving the performance of lecturers in the academic environment. The research was conducted using purposive sampling method, with a sample size of 55 lecturers. Data were collected through questionnaires in accordance with the research objectives. Data analysis used multiple linear regression, T test, F test, and coefficient of determination (R2) test. The results showed that work ethic has a positive and significant effect on lecturer performance, job transfer has a positive and significant effect on lecturer performance, and job satisfaction has a positive and significant effect on lecturer performance within the Faculty of Economics and Islamic Business. In conclusion, work ethic, job transfer, and job satisfaction have an important role in improving the performance of lecturers at the Faculty of Economics and Islamic Business, State Islamic University of Alauddin Makassar. Penelitian ini dilaksanakan pada Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar. Sampel menggunakan metode purposive sampling yaitu pengambilan sampel berdasarkan pertimbangan atau kriteria tertentu. Semua sampel berjumlah 55 responden pada Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar. Metode pengumpulan data yang digunakan adalah Wawancara langsung kepada pihak – pihak yang terlibat dengan masalah yang sedang dibahas serta memberikan kuesioner kepada dosen yang sesuai dengan penelitian yang dilakukan. Analisis data dilakukan dengan menggunakan analisa regresi linear berganda, Uji T-test, Uji F serta Uji Koefisien Determinasi (R2). Hasil analisis menunjukan bahwa etos kerja berpengaruh terhadap kinerja dosen di Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar; mutasi jabatan berpengaruh terhadap kinerja dosen di Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar; kepuasan kerja berpengaruh terhadap kinerja dosen di Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar; dan etos kerja, mutasi jabatan dan kepuasan kerja berpengaruh terhadap kinerja dosen di Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Alauddin Makassar; Kata Kunci: Etos kerja, Mutasi jabatan, Kepuasan kerja dan Kinerja dosen.